2009
DOI: 10.1111/j.1600-0625.2009.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and the skin – where do we stand?

Abstract: The common ectodermal origin of the skin and nervous systems can be expected to predict likely interactions in the adult. Over the last couple of decades much progress has been made to elucidate the nature of these interactions, which provide multidirectional controls between the centrally located brain and the peripherally located skin and immune system. The opioid system is an excellent example of such an interaction and there is growing evidence that opioid receptors (OR) and their endogenous opioid agonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(138 citation statements)
references
References 73 publications
(118 reference statements)
3
132
3
Order By: Relevance
“…Consistent with these observations, organotypic skin cultures containing DOPr-overexpressing keratinocytes displayed KRT10 repression and reduced epidermal thickness . Conversely, DOPrdeficient mice exhibited markedly increased expression of KRT10, hypertrophic wound edges, and delayed wound healing (Bigliardi-Qi et al, 2006;Bigliardi et al, 2009). Although the therapeutic potential of this type of response is undeniable, DOPr effects in the human skin were opposite to those described just above , underscoring the need for a better understanding of the human neuroendocrine skin system (Slominski, 2015) before any treatment strategy in wound healing can be envisioned.…”
Section: B D-opioid Receptors and Mitogen-activated Protein Kinase Smentioning
confidence: 69%
“…Consistent with these observations, organotypic skin cultures containing DOPr-overexpressing keratinocytes displayed KRT10 repression and reduced epidermal thickness . Conversely, DOPrdeficient mice exhibited markedly increased expression of KRT10, hypertrophic wound edges, and delayed wound healing (Bigliardi-Qi et al, 2006;Bigliardi et al, 2009). Although the therapeutic potential of this type of response is undeniable, DOPr effects in the human skin were opposite to those described just above , underscoring the need for a better understanding of the human neuroendocrine skin system (Slominski, 2015) before any treatment strategy in wound healing can be envisioned.…”
Section: B D-opioid Receptors and Mitogen-activated Protein Kinase Smentioning
confidence: 69%
“…However, depending on the chronicity of the wound and the stage of the healing process, some groups reported retarding effects in models of excisional wounds (Rook et al, 2008) and corneal abrasions (Sassani et al, 2003). Several comprehensive reviews summarized these findings and mostly concluded that topically applied opioids have the potential to improve wound healing and pain, and that -, ␦-, and -opioids may have differential effects (Sassani et al, 2003;Tegeder and Geisslinger, 2004;Schmelz and Paus, 2007;Chen et al, 2008;Bigliardi et al, 2009;LeBon et al, 2009;.…”
Section: Peripheral Pain Inhibitionmentioning
confidence: 99%
“…Analgesia after local (topical) opioid administration has been amply demonstrated in patients with various types of acute (e.g., orthopedic, dental, abdominal, urological, and eye surgery) and chronic pain (e.g., rheumatoid and osteoarthritis, oral mucositis, complex regional pain syndrome) (Azad et al, 2000;Dionne et al, 2001;Stein et al, 2003;Faktorovich and Basbaum, 2010). Several comprehensive reviews summarized these findings and mostly concluded that topically applied opioids have a potential to improve pain, albeit many clinical trials are small (Sawynok, 2003;Kopf et al, 2006;Bigliardi et al, 2009;LeBon et al, 2009).…”
Section: A Treatment Of Pain and Inflammationmentioning
confidence: 99%
See 2 more Smart Citations